Triad3A involved in the regulation of endotoxin tolerance and mycobactericidal activity through the NFκB‐nitric oxide pathway - Yongwei Qin; Jinliang Chen; Kuang Xu; Yang Lu; Feifan Xu; Jiahai Shi (Immunity, Inflammation and Disease)
Abstract Introduction Sepsis is characterized by an endotoxin tolerance phenotype that occurs in the stage of infection. Persistent bacterial infection can lead to immune cell exhaustion. Triad3A, an E3 ubiquitin ligase, negatively regulates its activation by TLR4. However, the effect of Triad3A on endotoxin tolerance and bactericidal ability in the state of endotoxin tolerance remains unclear. Methods Using single dose LPS and repeated LPS stimulated macrophage cell lines at indicated times, we investigated miR‐191, Tirad3A, TRAF3, TLR4, p‐P65, TNF‐α, IL‐1β, and iNOS expression, the effect of miR‐191 on Triad3A and TRAF3, gene loss‐of‐function analyses, the effect of Triad3A on TLR4, p‐P65, cytokine, and mycobactericidal activity in endotoxin tolerant cells infected with Mycobacterium marinum. Results Here we found that Triad3A is involved in regulating endotoxin tolerance. Our result also displayed that miR‐191 expression is downregulated in macrophages in the state of endotoxin tolerance. miR‐191 can directly bind to Triad3A and TRAF3. Additionally, knockdown of Triad3A can reverse the effect of decreasing TNF‐α and IL‐1β in endotoxin tolerant macrophages. Furthermore, we demonstrated that the TLR4‐NF‐κB‐NO pathway was associated with Triad3A and responsible for the killing of intracellular mycobacteria in a tuberculosis sepsis model. Conclusions These results provide new insight into the mechanisms of Triad3A induced tolerogenic phenotype in macrophages, which can help the better comprehension of the pathogenesis involved in septic shock with infection of Mycobacterium tuberculosis, and suggest that Triad3A may be a potential drug target for the treatment of severe septic tuberculosis.